2018
DOI: 10.1061/(asce)mt.1943-5533.0002221
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Particle Size Distribution of Organic Additives on the Microstructure of a Clay Ceramic and Its Thermal and Mechanical Properties

Abstract: In this study, the structure-property relationships of a clay ceramic with calibrated particles (10 or 50 μm) of polymethyl methacrylate (PMMA) were investigated to improve both the thermal and mechanical properties of fired clay bricks incorporating organic wastes. The structure was characterized using differential thermal, thermomechanical, and computed tomography analysis. It was found that the addition of 10-or 50-μm particles of PMMA resulted in a same 11% decrease of the thermal conductivity during the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The porosity of the brick will reduce its thermal conductivity. However, the size and type of porosity in the brick may matter . Nagy et al found that 10 and 50 μm pores resulted in the same reduction in thermal conductivity, but the smaller pores resulted in much greater compressive strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The porosity of the brick will reduce its thermal conductivity. However, the size and type of porosity in the brick may matter . Nagy et al found that 10 and 50 μm pores resulted in the same reduction in thermal conductivity, but the smaller pores resulted in much greater compressive strength.…”
Section: Resultsmentioning
confidence: 99%
“…However, the size and type of porosity in the brick may matter . Nagy et al found that 10 and 50 μm pores resulted in the same reduction in thermal conductivity, but the smaller pores resulted in much greater compressive strength. Sveda et al investigated the effects of pore size on thermal conductivity in clay bricks.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of the thermal conductivity is associated to the formation of pores, 36% for RA20 sample. In fact, the thermal conductivity decreases because of the low thermal conductivity of air in the newly formed pores [4].…”
Section: Resultsmentioning
confidence: 99%
“…However, agricultural biomass additives such as straw improve the properties of mud bricks [1].Consequently, studying these properties is a first step in evaluating the impact of the material not only on energy consumption, but also on indoor comfort [3]. The use of organic additives has increased worldwide, mainly due to their availability and also for their thermal, mechanical and environmental impact [4][5][6][7][8][9][10].As a result, the incorporation of biomass additives into clay bricks can reduce thermal conductivity and enhance compressive strengths. In our case, we used the argan shells as additives to the clay blocks; Argan trees are located mainly in the sous massa region.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 depicts the thermal analysis (DTA/TGA) of the mixed C&D waste at a temperature ranging from 30 to 1000 °C. The study is done in a dynamic manner, which means that the temperature rises continuously at a constant heating rate [51]. The weight loss is approximately 4% when the temperature is raised from 30 °C to 200 °C due to the removal of free water and interlayer OH-groups, and trapped carbon dioxide.…”
Section: Thermal Behaviormentioning
confidence: 99%